Investigation of nuclear reaction mechanisms of Nickel isotopes at various energies induced by alpha particles. (27th November 2019) - Asres, Yihunie Hibstie; Mathuthu, Manny; Ferede, Yinager Aschalew
Abstract: The excitation functions of 58 Ni ( α, n + 2p + α ) 55 Fe, 58 Ni ( α, n + 3p) 58 Co, 58 Ni ( α, n + p) 60 Cu, 58 Ni ( α, n + p+ α ) 56 Co, 58 Ni ( α, p) 61 Cu, 58 Ni ( α, p+ α ) 57 Co and 58 Ni ( α, 2n+p + α ) 55 Co reactions were studied for particle energies up to 70 MeV. The aim of this study is to investigate the reaction mechanisms of 58 Ni isotopes induced by alpha particle using computer code COMPLET and EXFOR database. Calculated results of the excitation functions are discussed and compared with the experimental data taken from database. Comparisons of theoretical nuclear reaction cross-section calculations give remarkable agreements with the experimental data taken from EXFOR database.